2013
DOI: 10.12659/msm.883743
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and purdue pegboard scores in individuals with hypertension after alternate nostril breathing, breath awareness, and no intervention

Abstract: BackgroundPreviously alternate nostril yoga breathing (anuloma-viloma pranayama) was shown to reduce the blood pressure (BP) in people with hypertension. An elevated BP has been associated with poor performance in certain tasks requiring attention and co-ordination. The Purdue pegboard task assesses manual dexterity and eye-hand co-ordination.Material/MethodsIn the present study there were ninety participants with essential hypertension. Their ages ranged from 20 to 59 years (group average age ±S.D., 49.7±9.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 22 publications
4
61
1
3
Order By: Relevance
“…Yoga based slow breathing exercise might increase vagal tone which shift sympathovagal balance towards parasympathetic predominance 9,[12][13][14][17][18]27 .Moreover SBE might also increases baroreflex sensitivity 28,29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoga based slow breathing exercise might increase vagal tone which shift sympathovagal balance towards parasympathetic predominance 9,[12][13][14][17][18]27 .Moreover SBE might also increases baroreflex sensitivity 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers had also seen improvement in cardiac autonomic nerve function status in many diseased conditions like asthma, essential hypertention including type 2 Diabetes mellitus (T2DM) after practicing yoga based exercise [14][15][16][17][18] .On the contrary, some other group of investigators reported almost no significant change in cardiac autonomic balance after slow breathing exercise in healthy subject 19 .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Eleven studies included subjects who were practitioners of breathing exercises and other components of yoga. [14][15][16][17][18][19][20][21][22][23][24] Their experience ranged from seven days to eighty-six months. Twenty-six studies did not provide details regarding prior yoga experience.…”
Section: Participants Characteristicsmentioning
confidence: 99%
“…Eighteen studies used technique which requires one nostril to breath in and opposite to breath out (for example, left nostril to breath in and right nostril to breath out, followed by right nostril to breath in and left nostril to breath out). 4,6,[14][15][16][17][18][19][20][21][22][23]30,[32][33][34][35][36] Seven of these studies did not specify which nostril was blocked first or if they started with inhalation or exhalation. 6,15,16,19,22,30,36 In 14 studies, subjects were asked to hold their breath and/or were given specific duration for inhalation, breath retention and exhalation phase (Table 1 for details) while performing ANB.…”
Section: Alternate Nostril Breathing Techniquementioning
confidence: 99%
See 1 more Smart Citation